2021
DOI: 10.1002/rth2.12595
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D microscopy highlights altered von Willebrand factor α‐granule storage in patients with von Willebrand disease with distinct pathogenic mechanisms

Abstract: Background Platelets play a key role in hemostasis through plug formation and secretion of their granule contents at sites of endothelial injury. Defects in von Willebrand factor (VWF), a platelet α‐granule protein, are implicated in von Willebrand disease (VWD), and may lead to defective platelet adhesion and/or aggregation. Studying VWF quantity and subcellular localization may help us better understand the pathophysiology of VWD. Objective Quantitative analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…VWF is found in platelet alpha-granules (Figure 1A) and in keeping with several ultrastructural studies [18][19][20]29] we observed discrete volumes of VWF in eccentrically located subdomains within the encapsulation of a P-selectin positive alpha-granule membrane (Supplemental Figure 1). As observed previously [20,30,31],…”
Section: Vwf Propeptide Colocalizes With Mature Vwf In Eccentric Alph...supporting
confidence: 89%
See 4 more Smart Citations
“…VWF is found in platelet alpha-granules (Figure 1A) and in keeping with several ultrastructural studies [18][19][20]29] we observed discrete volumes of VWF in eccentrically located subdomains within the encapsulation of a P-selectin positive alpha-granule membrane (Supplemental Figure 1). As observed previously [20,30,31],…”
Section: Vwf Propeptide Colocalizes With Mature Vwf In Eccentric Alph...supporting
confidence: 89%
“…A number of studies have focused on the role of platelet derived VWF in hemostasis [53][54][55][56][57]. VWD patients with mild and severe circulating VWF deficiencies who still have residual platelet VWF show a milder clinical phenotype [20,58]. Platelet VWF has also been reported to be important for DDAVPrelated amelioration of bleeding times in subgroups of type 1 VWD patients [59].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations